Dramas de hontem: imprensa, criminalidade e a crônica policial em são paulo (1910-1920) - Diniz, Mônica (2021)
This research aims to analyze the way in which the São Paulo newspapers A Gazeta and Correio Paulistano constructed a narrative about crime and criminals in the city of São Paulo between the period 1910 and 1920, a moment of great importance for print in Brazil. The fundamental point of the study is the analysis of how police notes referred to crime and its justifications, sometimes loaded with values, judgments and stereotypes about the subjects who occupied the streets, squares, various establishments in the city. During this period, the city was undergoing social, economic and urban transformation, in view of this, we sought to relate the police chronicles with the concept of the city that was being built. The police chronicles that deal with crimes designated here as "blood" and "misdemeanor" were selected, distinct categories to which we clarify. For this research, we considered working with printed sources such as the periodicals Correio Paulistano and A Gazeta, as well as chroniclers of the time and documents from the Reports of Chiefs of Police and Statistics on the city